Bisection Based Heuristic Technique to Resolve Sink Mobility in WSNs - Chhabra, Chetna; Singh, Yudhvir (International Journal of Computer Sciences and Engineering, 2019)
Sensor nodes of WSN have some degree of source of energy whilst they miles deploy in actual moment surroundings. The whole network depend upon this power to detect an event, collect information from surroundings, data aggregation and talk with base station or else sink to supply the collect statistics. The important challenges are how to increases the network lifetime using less power resource. Paper has shown that nodes close to the sink expend their influence energy faster than the nodes because of heavy operating cost messages from nodes that some distance far away from sink node. Sensors nearly sink are mutual by larger sensors to sink path therefore consume extra energy. The problem is known as hotspot problem, ends in a premature disconnection of the network. Hence Mobile sinks help achieving uniform energy-intake and implicitly offer load-balancing all the way through the network and the “Hotspot” trouble is alleviate. As well, they show of network can be better in terms of lifetime higher coverage and short reply time.